Numerical study on effect of oscillation center position on heat transfer and flow internal tube. (July 2019) - Tao, Hanzhong; Rui, Lei; Li, Wei; Cheng, Jianjie
Highlights: The effect of oscillation center on heat transfer and floe performance in an oscillating tube was investigated numerically. Heat transfer enhancement increased with increase in the distance between oscillation center and tube inlet. Flow resistance had a lower value at the first half and a higher value at the second half than static tube. Oscillation motion generated radial velocity and secondary flow which led to heat transfer enhancement. Abstract: Three-dimensional flow and convective heat transfer was modelled and was discreted by FVM to investigate the effect of oscillation center position on heat transfer and flow internal a smooth round tube in the present study. The heat transfer performance was measured by Nusselt number and flow capacity was measured by Darcy friction factor. The numerical results showed that heat transfer was enhanced and the enhancement increased with increase in the distance between oscillation and inlet. More over the fluctuation of Nu increased as the distance between oscillation and inlet increased. However, flow resistance was lower than static tube when oscillation center at the first half of tube and higher than static tube when oscillation center at the second half of tube including center point. In addition, the secondary flow and radial velocity was created by oscillation motion, which was the reason why heat transfer was enhanced.